2000
DOI: 10.1073/pnas.97.26.14578
|View full text |Cite
|
Sign up to set email alerts
|

Changing T cell specificity by retroviral T cell receptor display

Abstract: The diversity of the T cell receptor (TCR) repertoire is limited, because of the processes of positive and negative T cell selection. To obtain T cells with specificities beyond the immune system's capacity, we have developed a strategy for retroviral TCR display. In this approach, a library of T cell variants is generated in vitro and introduced into a TCR-negative murine T cell line by retroviral transfer. We document the value of TCR display by the creation of a library of an influenza A-specific TCR and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…But, even if our findings are not universally true for all TCRs, they are of significant importance. With sufficient care, it should be possible to choose or even artificially generate TCRs that display optimized quality (18,87,88).…”
Section: Discussionmentioning
confidence: 99%
“…But, even if our findings are not universally true for all TCRs, they are of significant importance. With sufficient care, it should be possible to choose or even artificially generate TCRs that display optimized quality (18,87,88).…”
Section: Discussionmentioning
confidence: 99%
“…The CD28-negative variant Jurkat cell line J.RT3-T3.5 was grown in Iscove's modified Dulbecco's medium (Life Technologies, Paisley, Scotland) with 5% FCS (BioWhittaker). Jurkat cells were transduced with pMX vectors encoding CD28 wt or CD28 KNI by using a transduction protocol as described (17) and sorted for CD28-expressing cells. A total of 2 ϫ 10 7 Jurkat͞CD28 wt or Jurkat͞CD28 KNI cells (in 500 l PBS) was stimulated with 10 g͞ml anti-CD28 mAb 37.51 in the presence of 0.1 mM pervanadate for 20 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that TCR reconstruction on TCR-deficient T cells is advantageous to investigate how the TCR-pMHC interaction influences T cell activation (27)(28)(29)(30) because primary T cells can increase or decrease their sensitivity/avidity for an epitope through changes in their inhibitory receptor expression and membrane organization as well as via a redistribution of signaling molecules in ϩ cells isolated from an HIV-negative donor were pulsed with various concentrations of VY8 or RY11 peptide (A), infected with recombinant vaccinia virus expressing Nef SF2 (B), or infected with HIV-1 (C) and then mixed with the indicated CTL clones. To obtain relative specific lysis values, the cytotoxic activity toward the same target cells not pulsed with peptide, infected with vaccinia virus alone (i.e., lacking nef expression) or infected with HIV-1 ⌬nef variant was determined in parallel and was deducted as a background value.…”
Section: Functional Reconstruction Of Tcrs On Tcr-deficient T Cellsmentioning
confidence: 99%